GAUTIER H.A JUYNBOLL’S PERSPECTIVE ON ‘ADĀLAḦ AL-ṢAḤĀBAH - Mahmud Wafi (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Ṣaḥābaḧ is the first generation who believe to the Prophet Muḥammad [p.b.u.h] and accepted the teachings of Islām (the ḥadīts of the Prophet) directly from Him. They are very obedient to the Prophet so that they may not dare to betray and lie intentionally in the narration of ḥadīts. They are ‘adil generally. Muslims believe that whole companions have ‘adālaḧ quality, which is famous by a dictum: kullu ṣaḥābaḧ ‘udūl. Furthermore, this belief has come as something approved theologically. This concept becomes stronger when the hadith criticism, traditional scholars are more oriented sanad which has implications for the placement of narrators personality in a position that can not be ignored. This is clearly different from Juynboll, he is one of the Orientalists who came from Netherland who developed the theory of common linkThe conclusion of this research that Juynboll denies the method of hadith criticism. He claims that this theory occurred in the evolutive schema, and is the creation of muḥaddits. On the other hand, the author views that the denial of Juynboll for collective ta‘dīl is one of the instruments to strengthen the theory of common link.